Rescaled range analysis of pluviometric records in SA o pound Paulo State, Brazil - Salomao, L. R. [UNESP]; Campanha, J. R. [UNESP]; Gupta, H. M. [UNESP] (Springer Wien, 2009)
This paper presents an analysis of pluviometric precipitation time series obtained from 45 data collection points, with daily rain measurements (in mm), from 45 counties within the nine climatic regions of the state of SA o pound Paulo, mostly for the period of 1950-1997. SA o pound Paulo State (Brazil) is situated between the inter-tropical climatic zone, dominated by tropical and equatorial masses, and the sub-tropical climatic zone controlled by tropical and polar air masses. Due to this location the State can be divided into three climatic zones: south-east and south-west, which are permanently humid, and north with a well defined dry period. Rescaled range analysis, or R/S analysis, has been used to investigate the scale properties of the time series. We found two clear values for the Hurst exponent, one for a period of 10 to 200 days (H(1)), and another for a period above 210 days (H(2)). The value of H(1) lies between 0.6 to 0.7 for all climatic zones indicating characteristics of persistence. However, H(2) is (i) close to 0.5 for the littoral area, showing random characteristics, (ii) close to 0.6 for mountain areas, indicating persistence characteristics, and (iii) close to 0.4 for the plane area, irrespective of whether the climate is dry or humid, and shows anti-persistence characteristics.